A method for preparing electrolytic copper powder for electric contact
By using high-purity cathode copper and electrolyte pre-purification technology, combined with automatic powder dropping and synergistic powder washing method, the problem of high carbon, nitrogen and sulfur content in electrolytic copper powder is solved, and the industrial production of low-impact electrolytic copper powder is achieved, meeting the performance requirements of electrical contacts and reducing production costs.
Patent Information
- Application Number
- CN202411988054.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
AI Technical Summary
When used in electrical contacts, the existing electrolytic copper powder has high carbon, nitrogen and sulfur content, which affects the conductivity and other properties, and the production process fails to effectively control the content of these impurity elements.
High-purity cathode copper is used as the anode, and the electrolyte pre-purification and automatic powder dropping technology are used to reduce the contamination of copper powder by the electrolytic process, and the synergy between soap liquid and polyol compounds are used in the powder washing step to reduce the use of traditional powder washing additives and reduce the impurity content.
The carbon, nitrogen and sulfur content of impurities in electrolytic copper powder products has been significantly reduced, and the quality requirements of electrical contact products have been met, which has improved production efficiency and reduced costs.
Abstract
Description
Technical Field
[0001] The invention relates to the field of powder metallurgy, and in particular to a method for preparing electrolytic copper powder for electric contacts. Background Art
[0002] An electrical contact is a contact part between two conductors or between a conductor and a semiconductor that allows current to flow. As a core component in medium and high voltage switchgear, electrical contacts play a core role in the conduction, disconnection and current conversion of circuits. They are widely used in various high-voltage load switches, SF6 circuit breakers, on-load tap changers, large breaking capacity disconnectors and earthing switches. They are the key connection link for electrical equipment to complete various electrical functions, and their performance directly affects the quality and service life of these electrical appliances.
[0003] Electrical contacts can be made of pure metals with good electrical conductivity (such as gold, silver, copper, etc.), alloys (such as silver-copper alloy, silver-nickel alloy, copper-tungsten alloy, etc.) or composite materials (such as metal ceramics or metal-nonmetal composite powders, etc.). In some occasions that are sensitive to cost but have certain requirements for electrical conductivity, copper is one of the preferred materials, and electrolytic copper powder is usually used.
[0004] The production of electrolytic copper powder is based on the principle of electrolytic refining. Generally, copper sulfate solution is used as the electrolyte, copper plate is used as the anode, and stainless steel plate or titanium plate is used as the cathode. Under the action of direct current, the anode copper plate undergoes an oxidation reaction and dissolves into the electrolyte. The copper ions obtain electrons on the cathode surface and are reduced to metallic copper and deposited. After the steps of powder dropping, powder washing, drying, screening, etc., high-purity electrolytic copper powder is obtained.
[0005] The national standard GB5246-2023 "Electrolytic Copper Powder" only stipulates that the iron content shall not exceed 0.01% (mass), the lead content shall not exceed 0.03%, and the oxygen content shall not exceed 0.15%, while the total content of other impurity elements shall not exceed 0.035%. However, when actually used in electrical contacts, the carbon, nitrogen, and sulfur contents have a relatively large impact on their performance. When copper, especially electrolytic copper powder, is used as the raw material for electrical contacts, the carbon, nitrogen, and sulfur contents in the electrolytic copper powder need to be strictly controlled.
[0006] At present, the electrolytic copper powder produced according to the conventional technology in the industry cannot meet the requirements of electrolytic copper powder for electric contacts, especially the relatively high carbon, nitrogen and sulfur content, which seriously affects the conductivity and other properties of the electric contacts. The reasons may include: the anode plate is generally used as the production raw material, and the anode plate needs to use charcoal and graphite in the production process, which will bring carbon into the product; various additives added in the electrolysis process will increase the carbon and sulfur content of the product; soap solution needs to be added in the powder washing process, which will increase the carbon content; the antioxidant added in the subsequent process will increase the nitrogen and carbon content of the product, so that the carbon, nitrogen and sulfur content in the electrolytic copper powder produced is relatively high.
[0007] The production process of electrolytic copper powder can be specifically referred to the following documents: "Research on Antioxidation Technology of Electrolytic Copper Powder", Li Jizhou, Master's Thesis of Central South University of Technology, 1999; "Electrolytic Preparation of Metallic Copper Powder", Yang Yuqi, Copper Industry Engineering, Issue 3, 2007; "Effect of Process Conditions on Preparation of Copper Powder by Electrodeposition", Guo Xueyi et al., Journal of University of Science and Technology Beijing, Vol. 33, Issue 2, 2011.
[0008] Chinese patent document CN103866352A is a patent for electrolytic copper powder related technology previously applied for by the applicant, comprising the following steps: first, inserting the raw material electrolytic copper plate into a conductive copper bar as a copper cathode plate and entering the electrolytic cell for electrolysis, filtering and washing the obtained electrolytic copper powder and the mixed solution containing the electrolyte, drying and reducing the wet electrolytic copper powder, and then crushing and screening; the electrolytic process uses an electrolyte with a copper ion concentration of 5-7g / L, a sulfuric acid concentration of 120-150g / L, an electrolysis temperature of 45-55°C, an electrolytic cell current of 13000A, a powder scraping time of 30-40 minutes / time, and the electrolyte is fed in a direction parallel to the cathode and anode plates. The electrolytic copper powder production method of the present invention eliminates the process of melting electrolytic copper and then casting it into an anode plate of a certain specification and shape in the traditional original process, effectively reduces the production cost, and also improves the quality of the produced electrolytic copper powder. The produced electrolytic copper powder is ≤200 mesh and has high purity. The voltage in the electrolytic cell can be 1.6-1.8 volts to carry out normal and effective electrolysis operation, which greatly reduces energy consumption. In addition, the electrolysis efficiency can reach 80-85%.
[0009] Chinese patent document CN102009169A discloses an electrolytic copper powder and a method for producing the electrolytic copper powder, the purpose of which is to obtain an electrolytic copper powder that can be molded with high strength without causing the dendrites of the electrolytic copper powder to develop beyond a necessary level and having improved moldability compared with conventional electrolytic copper powders. In order to enhance the strength of the electrolytic copper powder itself and precipitate an electrolytic copper powder that can be molded with high strength, the size of the microcrystals constituting the electrolytic copper powder is miniaturized, and in the method for producing the electrolytic copper powder in which the electrolytic copper powder is precipitated by passing an electric current through an electrolyte, the electrolyte is a solution in which one or more selected from tungstates, molybdates, and sulfur-containing organic compounds are added to an aqueous copper sulfate solution.
[0010] When the electrolytic copper powder prepared by the above prior art is actually used in electrical contacts, the influence of the carbon, nitrogen and sulfur contents on the performance of the electrical contacts is not particularly considered, and the carbon, nitrogen and sulfur contents in the electrolytic copper powder are not strictly controlled, resulting in excessive contents of these impurity elements. Summary of the invention
[0011] The purpose of the present invention is to solve the above technical problems and provide a method for preparing electrolytic copper powder for electrical contacts, so as to realize the industrial production of low-nitrogen, low-sulfur and low-carbon electrolytic copper powder by optimizing the process and changing the types of additives.
[0012] The present invention is mainly achieved through the following technical solutions.
[0013] A method for preparing electrolytic copper powder for electric contacts, comprising the following steps: 1) preparation of anode, cathode and electrolyte solution; 2) electrolysis; 3) powder dropping; 4) powder washing; 5) drying; 6) screening; characterized in that: the anode material is high-purity cathode copper, the electrolyte is pre-purified first, and the powder dropping step adopts automatic powder dropping. Directly using high-purity cathode copper as the anode for direct plate electrolysis avoids the carbon impurities introduced by charcoal and graphite required in the production process of traditional anode plates; using electrolyte pre-purification system and automatic powder dropping technology reduces the pollution of copper powder in the electrolysis process, and reduces the impurity nitrogen content, carbon content and sulfur content in the copper powder product; using automatic powder dropping technology to avoid impurities introduced by manual scraping.
[0014] Preferably, the high-purity cathode copper is grade A copper or standard copper No. 1. According to the provisions of the national standard GB / T467-2010 "Cathode Copper", grade A copper and standard copper No. 1 strictly limit the content of S element, which not only avoids the introduction of carbon impurities by charcoal and graphite, but also helps to control the impurity sulfur content of the electrolytic copper powder product of the present invention.
[0015] Preferably, the pre-purification of the electrolyte uses an integrated filter with a 160-mesh filter cloth. The pre-purification system is used to pre-purify the copper sulfate electrolyte, and the particulate impurities in the electrolyte are filtered on the filter cloth. The filtered electrolyte then enters the production system, which helps to control the amount of impurity carbon in the electrolytic copper powder product of the present invention. The used filter cloth can be cleaned or replaced every week.
[0016] It is also preferred that the additive used in the powder washing step is selected from a combination of soap solution or a corrosion inhibitor and a polyol compound. The soap solution mainly plays the role of dispersing, washing and preventing the agglomeration of the copper powder in the process of washing the electrolytic copper powder. The composition is a mixture of surfactants and other additives; at the same time, the soap solution can also wash away impurities and residues on the surface of the copper powder, which helps to control the content of impurities carbon, nitrogen and sulfur elements in the electrolytic copper powder product of the present invention. The role of the corrosion inhibitor is to prevent or slow down the contact and reaction of the copper powder with oxygen by forming a protective film on the surface of the copper powder, thereby extending the shelf life and service life of the copper powder. The use of polyol additives to replace some traditional powder washing additives reduces the use of traditional additives and helps to control the impurity content.
[0017] Preferably, the additive is a composition of soap solution and polyol compound, the mass ratio of which is 1:5-5:1, and the composition accounts for 0.01-5% of the total mass of the copper powder. Through the synergistic effect of soap solution and polyol compound and reducing the amount of soap solution used, it is possible to simultaneously control the low content of impurities carbon, nitrogen and sulfur in the electrolytic copper powder product of the present invention while satisfying the conventional function of powder washing, and no longer need to use corrosion inhibitors, which greatly reduces production costs.
[0018] Preferably, the powder washing step uses an integrated washing machine. This equipment can effectively reduce the additives brought into the surface of the electrolytic copper powder product of the present invention and reduce the sulfur and carbon content while ensuring sufficient washing.
[0019] Also preferably, a combined atmosphere of an inert gas and a reducing gas is used during the drying process, and the inert gas is selected from helium, neon, argon, krypton and xenon. The use of an inert gas can ensure that the copper powder is not oxidized, while a small amount of reducing gas (such as hydrogen) helps to reverse the oxidation of the copper powder; by using an inert gas that does not contain nitrogen, the introduction of impurity nitrogen elements that affect the quality of the copper powder is avoided in the copper powder, so as not to affect the performance of the electrical contact.
[0020] Also preferably, an antioxidant is added during the screening process, and the antioxidant is selected from a combination of benzotriazole (BTA) or benzoic acid and a passivator. These antioxidants can effectively prevent the electrolytic copper powder of the present invention from being oxidized during screening, storage and transportation, thereby ensuring the quality and performance of the copper powder after being used in electrical contacts. The present invention uses a passivator to replace part of the traditional antioxidant, reduces the amount of the traditional antioxidant used, further improves the antioxidant capacity of the product, and avoids the increase in carbon and nitrogen content caused by the traditional antioxidant.
[0021] Preferably, the additive is a composition of BTA and a passivating agent CY-502, the mass ratio of which is 1:5-5:1, and the composition accounts for 0.01-5% of the total mass of the copper powder. Through the synergistic effect of BTA and CY-502 and reducing the amount of BTA, the low content of impurities carbon, nitrogen and sulfur in the electrolytic copper powder product of the present invention can be optimally controlled while satisfying the conventional antioxidant effect.
[0022] Further preferably, the whole process of the method of the present invention adopts a closed production environment, which can reduce the pollution of dust in the air to the material and further reduce the content of impurity elements such as carbon, nitrogen and sulfur.
[0023] Beneficial Effects
[0024] The present invention uses high-purity cathode copper as an anode for direct plate electrolysis, thereby avoiding carbon impurities introduced by charcoal and graphite required in the traditional anode plate production process; using an electrolyte pre-purification system and automatic powder dropping technology, reducing the contamination of copper powder during the electrolysis process, and reducing the impurity nitrogen content, carbon content and sulfur content in the copper powder product; and adopting automatic powder dropping technology, avoiding impurities introduced by manual powder scraping.
[0025] The present invention can control the low content of impurities carbon, nitrogen and sulfur in the electrolytic copper powder product of the present invention while meeting the conventional function of powder washing through the synergistic effect of soap solution and polyol additives and reducing the use amount of conventional powder washing additives in the powder washing step, and no longer needs to use corrosion inhibitors, which greatly reduces production costs. The present invention further adopts an integrated washing machine, which can effectively reduce the additives brought into the surface of the electrolytic copper powder product of the present invention while ensuring sufficient washing, and reduce the sulfur and carbon content.
[0026] The present invention uses a combined atmosphere of inert gas and reducing gas during the drying process. The use of inert gas can ensure that the copper powder is not oxidized, and a small amount of reducing gas helps to reverse the oxidation of the copper powder. By using an inert gas that does not contain nitrogen, the introduction of impurity nitrogen elements that affect the quality of the copper powder is avoided in the copper powder, so as not to affect the performance of the electrical contact.
[0027] The present invention adds antioxidants during the screening process, and these antioxidants can effectively prevent the electrolytic copper powder of the present invention from being oxidized during the screening, storage and transportation processes, thereby ensuring the quality and performance of the copper powder after being used in electrical contacts. The present invention uses a passivator to replace part of the traditional antioxidants, reduces the amount of the traditional antioxidants used, further improves the antioxidant capacity of the product, and avoids the increase in carbon and nitrogen content caused by the traditional antioxidants.
[0028] The present invention adopts a closed production environment in the whole process, which can reduce the pollution of dust in the air to the material and further reduce the content of impurity elements such as carbon, nitrogen and sulfur.
[0029] By means of the improved electrolytic copper powder production process of the present invention, the impurity carbon of the electrolytic copper powder product can be ≤200ppm, nitrogen ≤40ppm, and sulfur ≤40ppm, and the electrolytic copper powder product can meet the quality requirements of the electric contact product. DETAILED DESCRIPTION
[0030] The following is further described in detail through specific implementation methods. However, it should be pointed out that the following embodiments of the present invention are only for better illustrating the content of the present invention, but do not mean that the content of the present invention is limited to the examples. Therefore, those skilled in the art can make non-essential improvements and adjustments to the implementation scheme according to the above invention content, which still belongs to the protection scope of the present invention and is subject to the protection scope of the attached claims.
[0031] The electrical contact referred to in the present invention refers to the contact part between two conductors or between a conductor and a semiconductor that can allow current to pass. As a core component in medium and high voltage switchgear, the electrical contact plays a core role in the conduction, disconnection and current conversion of the circuit. The electrical contact can be made of pure metals with good electrical conductivity (such as gold, silver, copper, etc.), alloys (such as silver-copper alloys, silver-nickel alloys, copper-tungsten alloys, etc.) or composite materials (such as metal ceramics or metal-non-metal composite powders, etc.). Among them, copper is an excellent conductive material with high electrical conductivity and good thermal conductivity, second only to silver; its resistivity is low, it can effectively conduct current, and the price is relatively reasonable. Copper has good chemical stability and is not easily corroded under normal conditions, but may oxidize in certain specific harsh environments (such as humid environments containing corrosive gases). Copper is widely used in various medium and low voltage and current electrical contacts, such as electrical contacts in general household switches, sockets and some industrial control electrical appliances. In some occasions that are sensitive to cost but have certain requirements for electrical conductivity, copper is one of the preferred materials.
[0032] The electrolytic copper powder referred to in the present invention refers to the copper powder produced based on the principle of electrolytic refining, generally using copper sulfate solution as the electrolyte, copper plate as the anode, and stainless steel plate or titanium plate as the cathode. Under the action of direct current, the anode copper plate undergoes an oxidation reaction and dissolves into the electrolyte, and the copper ions obtain electrons on the cathode surface and are reduced to metallic copper and deposited. Its main electrode reactions are as follows:
[0033] Anodic reaction: Cu-2e-→Cu2+
[0034] Cathode reaction: Cu2++2e-→Cu
[0035] As the electrolysis process proceeds, copper on the cathode is continuously deposited and gradually forms powder, and electrolytic copper powder products are obtained through subsequent processing procedures. The anode copper plate can be selected with a purity of more than 99.9%, and its impurity content directly affects the purity and quality of the electrolytic copper powder. Before use, the anode copper plate is cleaned to remove oil stains, oxide layers and other impurities on the surface to ensure the uniformity and stability of the anode dissolution. The cathode material is usually a stainless steel plate or a titanium plate. When selecting, its conductivity, corrosion resistance and surface flatness should be considered. The new cathode plate needs to be pretreated, such as polishing, cleaning and activation treatment, to improve the deposition effect and stripping performance of copper powder on the cathode. The main components of the electrolyte are copper sulfate and sulfuric acid. Copper sulfate provides a source of copper ions, and sulfuric acid is used to improve the conductivity and stability of the electrolyte. Generally, copper sulfate is dissolved in deionized water to prepare a solution with a concentration of 150-250g / L, and then an appropriate amount of sulfuric acid is added to make the sulfuric acid concentration reach 50-100g / L. In addition, a small amount of additives, such as chloride ions (added in the form of hydrochloric acid, with a concentration of about 20-50 ppm), can be added to improve the particle size distribution and surface quality of the copper powder.
[0036] During the electrolysis process, the electrolytic cell is made of acid-resistant and well-insulated materials, such as plastic cells. The cleaned anode copper plates and cathode plates are installed in parallel in the electrolytic cell at a certain distance (usually 20-50mm), and the insulation between the electrodes and the electrolytic cell is ensured to be good. The electrodes are connected in series or in parallel, and are selected according to the performance of the power supply equipment and production requirements to ensure that the current is evenly distributed on each electrode. Connect the DC power supply and adjust the current density to the appropriate range (usually 100-500A / m 2 ). The current density directly affects the particle size, deposition rate and quality of the copper powder. A lower current density is conducive to the production of larger copper powder particles, but the production efficiency is lower; a higher current density will make the copper powder particles finer, but may lead to powder agglomeration and increased impurity inclusions. During the electrolysis process, the stability of the current density must be strictly controlled by means of a constant current power supply device and real-time current monitoring. At the same time, the temperature of the electrolyte will increase due to the passage of current, and the temperature must be controlled at 40-60°C through a circulating cooling system. Too high a temperature will accelerate the evaporation and decomposition of the electrolyte, affect the stability of the solution components, and cause the copper powder particles to become coarser; too low a temperature will reduce the conductivity of the electrolyte, increase the energy consumption of electrolysis, and may cause uneven deposition of copper ions.
[0037] When the copper powder deposition on the cathode reaches a certain thickness (generally 0.5-2mm), the mechanical vibration device is started to make the copper powder fall off from the cathode surface. The vibration frequency is usually controlled at 50-200Hz, and the amplitude is between 1-5mm. Appropriate vibration parameters can make the copper powder fall off evenly, avoid the formation of large agglomerates, and reduce damage to the cathode plate. The vibration device can use an eccentric wheel vibrator or an electromagnetic vibrator, which is installed at the bottom or side of the electrolytic cell, and transmits the vibration to the cathode plate through a rigid connection with the electrolytic cell. On the basis of mechanical vibration, the ultrasonic-assisted technology can be combined to further improve the shedding efficiency and dispersibility of the copper powder. The high-frequency vibration wave generated by the ultrasonic generator is transmitted to the electrolyte through the transducer. The ultrasonic power is generally controlled at 500-2000W, and the action time is 5-15 minutes. Ultrasonic vibration can destroy the adhesion between the copper powder and the cathode, making the copper powder easier to fall off, and helps to disperse the agglomerated copper powder particles to obtain a copper powder product with a more uniform particle size.
[0038] After collecting the detached copper powder, first rinse it with a large amount of deionized water to remove the electrolyte attached to the surface. The mass ratio of water to copper powder is generally controlled between 5:1 and 10:1. The water washing operation is carried out in a water washing tank with a stirring device. The stirring speed is 100-300r / min and the water washing time is about 10-20 minutes. Through sufficient stirring and water flushing, the copper powder is fully dispersed, most of the impurities such as free acid and copper sulfate are washed away, and the impurity content in the copper powder is initially reduced. The copper powder after the initial water washing is then pickled with a dilute sulfuric acid solution to further remove oxides and impurities on the surface. The concentration of dilute sulfuric acid is generally 5-10%, the pickling temperature is controlled at 30-40℃, and the pickling time is 5-10 minutes. The copper powder should be stirred continuously during the pickling process to ensure uniform pickling effect. After pickling, the copper powder is quickly rinsed with deionized water until the pH value of the washing water is close to neutral to prevent the acid residue from having an adverse effect on the quality of the copper powder, such as causing oxidation or corrosion of the copper powder during subsequent storage. The copper powder after pickling can be deeply washed with water by multi-stage countercurrent washing to further reduce the impurity content in the copper powder. Set up 3-5 levels of washing tanks, and the water in each level of washing tank flows in reverse order, so that the copper powder is always in contact with cleaner water during the washing process, improving the washing efficiency. The mass ratio of water to copper powder can be increased to 10:1 to 20:1 during the deep washing process, and the total washing time is about 30-60 minutes. Through multiple washings, it is ensured that the impurity content of sulfate ions, chloride ions and other impurities in the copper powder meets the product quality standards, and the purity and chemical stability of the copper powder are improved.
[0039] Various additives can also be used in the powder washing step to improve the quality and performance of copper powder. Among them, soap solution and corrosion inhibitor are commonly used types of additives. Soap solution mainly plays the role of dispersing, washing and preventing copper powder from agglomerating during the washing process of electrolytic copper powder. Although the specific soap solution ingredients may vary depending on the manufacturer and process, they are usually based on a mixture of surfactants and other additives, and suitable specific soap solution products can be purchased commercially as needed. These surfactants can reduce the surface tension of water, making it easier for water to penetrate between copper powder particles, thereby effectively dispersing the copper powder particles. At the same time, soap solution can also wash away impurities and residues on the surface of copper powder to improve the purity of copper powder. Corrosion inhibitors are mainly used to prevent oxidative corrosion of copper powder during the preparation of electrolytic copper powder. Since copper powder has a large specific surface area and surface energy, it is easy to oxidatively corrode and deteriorate under natural environmental conditions. The role of the corrosion inhibitor is to prevent or slow down the contact and reaction of copper powder with oxygen by forming a protective film on the surface of copper powder, thereby extending the shelf life and service life of copper powder. Common types of corrosion inhibitors include: inorganic corrosion inhibitors (such as nitrites, silicates, etc.), which usually play a protective role by forming complexes or precipitates with metal ions on the surface of copper powder; organic corrosion inhibitors (such as benzotriazole (BTA), gelatin, etc.), which have better adsorption and film-forming properties and can form a dense protective film on the surface of copper powder. Especially benzotriazole, it can form a stable BTA-Cu complex film on the surface of copper powder, effectively preventing the oxidation corrosion of copper powder. In practical applications, the selection and dosage of corrosion inhibitors need to be determined according to the type, particle size, use environment and required antioxidant properties of copper powder. At the same time, attention should also be paid to the compatibility of corrosion inhibitors with electrolytes and their effects on the electrolysis process.
[0040] Then put the washed copper powder into a vacuum drying oven for drying. The vacuum degree is controlled between -0.08 and -0.1MPa, and the drying temperature is between 80-120℃. In a vacuum environment, moisture can evaporate quickly at a lower temperature, avoiding oxidation of copper powder at high temperature, while reducing drying time and improving production efficiency. During the drying process, the copper powder should be stirred continuously to volatilize the moisture evenly and prevent the copper powder from agglomerating. The stirring method can be mechanical stirring or gas stirring. Mechanical stirring is achieved by a stirring paddle installed in the drying oven, and gas stirring uses the inert gas (such as nitrogen) flow introduced to drive the copper powder to turn. For some products that are not very strict with oxidation requirements, hot air drying can also be used. Place the copper powder in a drying device and pass dehumidified and purified hot air. The hot air temperature is controlled at 100-150℃ and the wind speed is between 1-3m / s. The moisture evaporates quickly through full contact between hot air and copper powder. However, during the hot air drying process, the drying time and temperature must be strictly controlled to minimize the contact time between copper powder and air and reduce the degree of oxidation. Continuous drying equipment, such as a tunnel dryer, can be used to dry the copper powder while it is flowing, thereby improving production efficiency.
[0041] Next, the dried copper powder is screened with a vibrating screen to obtain products with different particle size ranges. The vibration screening uses multiple layers of screens, and the screen apertures are arranged in order from large to small. For example, screens of different specifications such as 100 mesh, 200 mesh, and 325 mesh can be selected. Pour the copper powder into the vibrating screen, turn on the vibration motor, control the vibration frequency at 100-300Hz, and the amplitude between 0.5-2mm, so that the copper powder reciprocates on the screen. Through screens with different apertures, the copper powder is divided into different grades such as coarse powder, medium powder, and fine powder to meet the needs of different users. The screen frame of the vibrating screen is made of stainless steel, and the screen is made of high-precision woven mesh or punched mesh to ensure screening accuracy and durability. For some products with high requirements for particle size distribution, the screening accuracy can be further improved by combining airflow screening technology. The airflow screen uses the effect of airflow to suspend copper powder particles on the screen and separate them according to particle size. By adjusting the air flow speed and pressure, the copper powder is driven by the air flow to pass through the screen, and the fine powder passes through the screen into the collection device with the air flow, while the coarse powder remains on the screen. Airflow screening can effectively separate copper powders of similar particle sizes and improve the particle size uniformity and quality stability of the product. Airflow screening equipment usually consists of an air source, an airflow generator, a screening chamber and a collection device. The air source provides a stable airflow, the airflow generator accelerates the airflow and forms a specific flow field distribution, a high-precision screen is installed in the screening chamber, and the collection device is used to collect copper powder products of different particle sizes.
[0042] In order to prevent the copper powder from oxidizing during storage and use, it is usually necessary to add antioxidants to the copper powder product during or after the screening process. Common antioxidants include benzotriazole (BTA), 2-mercaptobenzimidazole (MBI), etc. These antioxidants can form a protective film on the surface of the copper powder to prevent oxygen from contacting the copper powder, thereby playing an antioxidant role. For example, BTA has a good antioxidant effect, and its addition amount is generally 0.1-0.5% of the mass of the copper powder. The specific addition amount can be adjusted according to the storage conditions and use requirements of the product. Antioxidants can be added to the copper powder by solution spraying or direct mixing. The solution spraying method is to dissolve the antioxidant in an appropriate amount of organic solvent (such as ethanol) to make a solution of a certain concentration, and then spray the solution evenly on the surface of the copper powder through a spray device, stirring while spraying to ensure that the antioxidant is evenly covered on the copper powder. The direct mixing method is to mix the antioxidant in powder form directly with the copper powder in a mixing device. The mixing time is generally 10-30 minutes, so that the antioxidant is evenly dispersed in the copper powder to achieve a good antioxidant effect. The mixing equipment can be a double cone mixer, V-type mixer and other high-efficiency mixing equipment to ensure the uniform mixing of the antioxidant and the copper powder.
[0043] In terms of the production standards of electrolytic copper powder, the national standard GB5246-2023 "Electrolytic Copper Powder" only stipulates that the iron content is not more than 0.01% (mass), the lead content is not more than 0.03%, and the oxygen content is not more than 0.15%, while the total content of other impurity elements is only not more than 0.035%. The determination method of the element content in electrolytic copper powder is carried out in accordance with the provisions of the same standard document, the national standard GB5121 "Chemical Analysis Methods for Copper and Copper Alloys" and other relevant standards.
[0044] The best process of the preparation process of the present invention is:
[0045] A sulfuric acid copper sulfate aqueous solution consisting of a copper concentration of 4-9 g / L and a sulfuric acid concentration of 100-150 g / L is prepared as an electrolyte, and an integrated filter with a 160-mesh filter cloth is used to pre-purify the electrolyte to obtain an electrolyte for production; wherein the 160-mesh filter cloth and its filter can be conventionally purchased on the market, and the 160-mesh size is only an average filter pore size, and in fact, filter cloths in the range of 140-180 meshes can be used;
[0046] After immersing a cathode made of a homemade pure copper plate and an anode made of high-purity cathode copper in an electrolyte maintained at a liquid temperature of 40-60°C, the electrolyte is charged at 500-1200A / m 2 The current density of the current flows through the two electrodes, and electrolytic copper powder is deposited on the cathode;
[0047] When the copper powder deposition on the cathode reaches 0.5-2mm, use a high-pressure water gun to blow off the copper powder on the cathode plate. The pressure is 0.3-0.7Mpa, the muzzle is 800mm wide, and the slit is 1mm. The parameters of the high-pressure gun can be adjusted appropriately according to the actual situation.
[0048] The collected copper powder is washed with a mass ratio of deionized water to copper powder of 5:1 to 10:1, and 0.01-5% of the mass of the copper powder is added to the deionized water for washing with soap solution, corrosion inhibitor and one or more of polyol compounds as powder washing additives, and the powder washing operation is carried out in an integrated washing machine with a stirring device, the stirring speed is 100-300r / min, and the washing time is 150-200 minutes. To enhance the washing effect, multiple multi-stage washing can be performed;
[0049] The cleaned copper powder is placed in a mesh belt furnace for drying at a temperature of 300-500°C; during the drying process, a mixed atmosphere of argon and hydrogen (volume ratio 5:1-10:1) is introduced at the same time, and the gas flow rate is controlled at 25L / h (average flow rate, which can fluctuate appropriately);
[0050] The dried copper powder is screened by a vibrating screen to obtain products with different particle size ranges (average particle size of 100 mesh, 200 mesh, 325 mesh, etc.), the vibration frequency is controlled at 100-300 Hz, and the amplitude is between 0.5-2 mm; during the screening process or after the screening, an antioxidant accounting for 0.01-5% of the total mass of the copper powder is added to the copper powder product, and the antioxidant is selected from one or more of benzotriazole (BTA), benzoic acid and passivator CY-502 (other passivators suitable for copper powder can also be selected according to actual needs); finally, the electrolytic copper powder product for electric contacts of the present invention is packaged and its quality grade is inspected.
[0051] The whole process of the process of the present invention adopts a closed production environment.
[0052] If the technology, instruments, equipment and materials used in the present invention are not particularly specified, any other technology, instruments, equipment and materials known to those skilled in the art that can achieve the same purpose may be used; even if the technology, instruments, equipment and materials used in the present invention are particularly specified, it does not mean that the present invention can only use these technologies, instruments, equipment and materials, which only represent the preferred embodiments of the present invention, and those skilled in the art can still use any other technology, instruments, equipment and materials known to those skilled in the art that can achieve the same purpose.
[0053] Example 1
[0054] A sulfuric acid copper sulfate aqueous solution consisting of a copper concentration of 6 g / L and a sulfuric acid concentration of 120 g / L is prepared as an electrolyte, and the electrolyte is pre-purified using an integrated filter with a 160-mesh filter cloth to obtain an electrolyte for production;
[0055] After immersing a cathode made of a homemade pure copper plate and an anode made of No. 1 standard high-purity cathode copper in an electrolyte maintained at a liquid temperature of 50°C, the electrolyte was charged at 800A / m 2 The current density of the current flows through the two electrodes, and electrolytic copper powder is deposited on the cathode;
[0056] When the copper powder deposition on the cathode reaches 1mm, use a high-pressure water gun to blow off the copper powder on the cathode plate. The pressure is 0.5Mpa, the muzzle is 800mm wide, and the slit is 1mm.
[0057] The collected copper powder was washed with deionized water and copper powder in a mass ratio of 8:1 in an integrated washing machine (product of Saideli Company) with a stirring device, the stirring speed was 200 r / min, and the washing time was 180 minutes;
[0058] The cleaned copper powder is placed in a mesh belt furnace for drying at a temperature of 400°C;
[0059] The dried copper powder is sieved by a vibrating screen to obtain products with different particle size ranges (average particle size of 100 mesh, 200 mesh, 325 mesh, etc.), the vibration frequency is controlled at 200 Hz, and the amplitude is 1 mm; finally, the electrolytic copper powder product for electrical contacts of the present invention is packaged and its quality grade is inspected.
[0060] The whole process of the process of the present invention adopts a closed production environment.
[0061] This solution uses pre-purification of the electrolyte before putting it into production, and uses automatic powder dropping technology. The impurity carbon, nitrogen and sulfur content of the copper powder product obtained by electrolysis are significantly reduced, as shown in Table 1.
[0062] Example 2
[0063] A sulfuric acid copper sulfate aqueous solution consisting of a copper concentration of 6 g / L and a sulfuric acid concentration of 120 g / L is prepared as an electrolyte, and the electrolyte is pre-purified using an integrated filter with a 160-mesh filter cloth to obtain an electrolyte for production;
[0064] After immersing a cathode made of a homemade pure copper plate and an anode made of No. 1 standard high-purity cathode copper in an electrolyte maintained at a liquid temperature of 50°C, the electrolyte was charged at 1200A / m 2 The current density of the current flows through the two electrodes, and electrolytic copper powder is deposited on the cathode;
[0065] When the copper powder deposition on the cathode reaches 1mm, use a high-pressure water gun to blow off the copper powder on the cathode plate. The pressure is 0.5Mpa, the muzzle is 800mm wide, and the slit is 1mm.
[0066] The collected copper powder was washed by using a mass ratio of deionized water to copper powder of 8:1 in an integrated washing machine with a stirring device, and a soap solution of 1% of the mass of the copper powder was added to the deionized water for washing as a washing additive, the stirring speed was 200 r / min, and the washing time was 200 minutes;
[0067] The cleaned copper powder is placed in a mesh belt furnace for drying at a temperature of 400°C;
[0068] The dried copper powder is sieved by a vibrating screen to obtain products with different particle size ranges (average particle size of 100 mesh, 200 mesh, 325 mesh, etc.), the vibration frequency is controlled at 200 Hz, and the amplitude is 1 mm; finally, the electrolytic copper powder product for electrical contacts of the present invention is packaged and its quality grade is inspected.
[0069] The whole process of the process of the present invention adopts a closed production environment.
[0070] This solution further removes the sulfur compounds remaining on the surface of the copper powder during the washing process. During the washing process, a soap solution additive is added to form a protective layer on the surface of the copper powder to reduce the reaction between the copper powder and oxygen. The impurity carbon, nitrogen and sulfur content of the copper powder product obtained by electrolysis is significantly reduced, as shown in Table 1.
[0071] Example 3
[0072] A sulfuric acid copper sulfate aqueous solution consisting of a copper concentration of 6 g / L and a sulfuric acid concentration of 120 g / L is prepared as an electrolyte, and the electrolyte is pre-purified using an integrated filter with a 160-mesh filter cloth to obtain an electrolyte for production;
[0073] After immersing the cathode composed of a self-made copper plate and the anode composed of No. 1 standard high-purity cathode copper in an electrolyte maintained at a liquid temperature of 50°C, the electrolyte was charged at 500A / m 2 The current density of the current flows through the two electrodes, and electrolytic copper powder is deposited on the cathode;
[0074] When the copper powder deposition on the cathode reaches 1mm, use a high-pressure water gun to blow off the copper powder on the cathode plate. The pressure is 0.5Mpa, the muzzle is 800mm wide, and the slit is 1mm.
[0075] The collected copper powder was washed with a mass ratio of deionized water to copper powder of 8:1, and soap solution, corrosion inhibitor benzotriazole and polyethylene glycol (the mass ratio of soap solution, corrosion inhibitor and polyethylene glycol was 1:1:1) of 5% of the mass of the copper powder were added to the deionized water for washing as powder washing additives, and the powder washing operation was carried out in an integrated washing machine with a stirring device, the stirring speed was 200 r / min, the washing time was 150 minutes, and washing was performed twice;
[0076] The cleaned copper powder is placed in a mesh belt furnace for drying at a temperature of 400°C;
[0077] The dried copper powder is sieved by a vibrating screen to obtain products with different particle size ranges (average particle size of 100 mesh, 200 mesh, 325 mesh, etc.), the vibration frequency is controlled at 200 Hz, and the amplitude is 1 mm; finally, the electrolytic copper powder product for electrical contacts of the present invention is packaged and its quality grade is inspected.
[0078] The entire process adopts a closed production environment.
[0079] In this embodiment, during the powder washing process, a combination of soap solution, corrosion inhibitor benzotriazole and polyethylene glycol was added to improve the content of impurity elements and improve the product quality of the electrolytic copper powder of the present invention. Specific data are shown in Table 1.
[0080] Example 4
[0081] A sulfuric acid copper sulfate aqueous solution consisting of a copper concentration of 6 g / L and a sulfuric acid concentration of 120 g / L is prepared as an electrolyte, and the electrolyte is pre-purified using an integrated filter with a 160-mesh filter cloth to obtain an electrolyte for production;
[0082] After immersing the cathode composed of a self-made copper plate and the anode composed of No. 1 standard high-purity cathode copper in an electrolyte maintained at a liquid temperature of 50°C, the electrolyte was charged at 800A / m 2 The current density of the current flows through the two electrodes, and electrolytic copper powder is deposited on the cathode;
[0083] When the copper powder deposition on the cathode reaches 1mm, use a high-pressure water gun to blow off the copper powder on the cathode plate. The pressure is 0.5Mpa, the muzzle is 800mm wide, and the slit is 1mm.
[0084] The collected copper powder was washed with deionized water and copper powder in a mass ratio of 8:1, and soap solution and polyethylene glycol (the mass ratio of soap solution and polyethylene glycol was 1:2) were added to the deionized water for washing as powder washing additives, and the powder washing operation was performed in an integrated washing machine with a stirring device, the stirring speed was 200 r / min, the washing time was 150 minutes, and washing was performed 3 times;
[0085] The cleaned copper powder is placed in a mesh belt furnace for drying at a temperature of 400°C;
[0086] The dried copper powder is sieved by a vibrating screen to obtain products with different particle size ranges (average particle size of 100 mesh, 200 mesh, 325 mesh, etc.), the vibration frequency is controlled at 200 Hz, and the amplitude is 1 mm; finally, the electrolytic copper powder product for electrical contacts of the present invention is packaged and its quality grade is inspected.
[0087] The entire process adopts a closed production environment.
[0088] In this embodiment, during the powder washing process, a combination of soap solution and polyethylene glycol is added to improve the content of impurity elements and improve the product quality of the electrolytic copper powder of the present invention. Specific data are shown in Table 1.
[0089] Example 5
[0090] A sulfuric acid copper sulfate aqueous solution consisting of a copper concentration of 6 g / L and a sulfuric acid concentration of 120 g / L is prepared as an electrolyte, and the electrolyte is pre-purified using an integrated filter with a 160-mesh filter cloth to obtain an electrolyte for production;
[0091] After immersing a cathode made of a homemade pure copper plate and an anode made of No. 1 standard high-purity cathode copper in an electrolyte maintained at a liquid temperature of 50°C, the electrolyte was charged at 800A / m 2 The current density of the current flows through the two electrodes, and electrolytic copper powder is deposited on the cathode;
[0092] When the copper powder deposition on the cathode reaches 1mm, use a high-pressure water gun to blow off the copper powder on the cathode plate. The pressure is 0.5Mpa, the muzzle is 800mm wide, and the slit is 1mm.
[0093] The collected copper powder was washed with a mass ratio of deionized water to copper powder of 8:1 in an integrated washing machine with a stirring device at a stirring speed of 200 r / min for 180 minutes, and washed twice;
[0094] The cleaned copper powder was placed in a mesh belt furnace for drying at a temperature of 400°C. During the drying process, a mixed atmosphere of inert gas argon and hydrogen (volume ratio 8:1) was introduced to drive the copper powder to turn over, and the gas flow rate was controlled at about 25L / h.
[0095] The dried copper powder is sieved by a vibrating screen to obtain products with different particle size ranges (average particle size of 100 mesh, 200 mesh, 325 mesh, etc.), the vibration frequency is controlled at 200 Hz, and the amplitude is 1 mm; finally, the electrolytic copper powder product for electrical contacts of the present invention is packaged and its quality grade is inspected.
[0096] The entire process adopts a closed production environment.
[0097] In this embodiment, during the drying process, a combination of argon and a small amount of pure hydrogen is added as the atmosphere, which improves the content of impurity elements and improves the quality of the electrolytic copper powder product of the present invention. Specific data are shown in Table 1.
[0098] Example 6
[0099] A sulfuric acid copper sulfate aqueous solution consisting of a copper concentration of 6 g / L and a sulfuric acid concentration of 120 g / L is prepared as an electrolyte, and the electrolyte is pre-purified using an integrated filter with a 160-mesh filter cloth to obtain an electrolyte for production;
[0100] After immersing a cathode made of a homemade pure copper plate and an anode made of No. 1 standard high-purity cathode copper in an electrolyte maintained at a liquid temperature of 50°C, the electrolyte was charged at 800A / m 2 The current density of the current flows through the two electrodes, and electrolytic copper powder is deposited on the cathode;
[0101] When the copper powder deposition on the cathode reaches 1mm, use a high-pressure water gun to blow off the copper powder on the cathode plate. The pressure is 0.5Mpa, the muzzle is 800mm wide, and the slit is 1mm.
[0102] The collected copper powder was washed with a mass ratio of deionized water to copper powder of 8:1 in an integrated washing machine with a stirring device at a stirring speed of 200 r / min for 150 minutes, and washed twice;
[0103] The cleaned copper powder is placed in a mesh belt furnace for drying at a temperature of 400°C;
[0104] The dried copper powder is screened by a vibrating screen to obtain products with different particle size ranges (average particle size of 100 mesh, 200 mesh, 325 mesh, etc.), the vibration frequency is controlled at 200 Hz, and the amplitude is 1 mm; during the screening process or after the screening, an antioxidant accounting for 1% of the total mass of the copper powder is added to the copper powder product, and the antioxidant is a combination of benzotriazole (BTA) and a passivating agent CY-502 in a mass ratio of 1:3; finally, the electrolytic copper powder product for electric contacts of the present invention is packaged, and its quality grade is inspected.
[0105] The entire process adopts a closed production environment.
[0106] In this embodiment, during the screening process, a combination of BTA and passivating agent CY-502 was added to improve the content of impurity elements and improve the quality of the electrolytic copper powder product of the present invention. Specific data are shown in Table 1.
[0107] Example 7
[0108] A sulfuric acid copper sulfate aqueous solution consisting of a copper concentration of 6 g / L and a sulfuric acid concentration of 120 g / L is prepared as an electrolyte, and the electrolyte is pre-purified using an integrated filter with a 160-mesh filter cloth to obtain an electrolyte for production;
[0109] After immersing a cathode made of a homemade pure copper plate and an anode made of No. 1 standard high-purity cathode copper in an electrolyte maintained at a liquid temperature of 50°C, the electrolyte was charged at 800A / m 2 The current density of the current flows through the two electrodes, and electrolytic copper powder is deposited on the cathode;
[0110] When the copper powder deposition on the cathode reaches 1mm, use a high-pressure water gun to blow off the copper powder on the cathode plate. The pressure is 0.5Mpa, the muzzle is 800mm wide, and the slit is 1mm.
[0111] The collected copper powder was washed with a mass ratio of deionized water to copper powder of 8:1 in an integrated washing machine with a stirring device at a stirring speed of 200 r / min for 200 minutes, and washed twice;
[0112] The cleaned copper powder is placed in a mesh belt furnace for drying at a temperature of 400°C;
[0113] The dried copper powder is screened by a vibrating screen to obtain products with different particle size ranges (average particle size of 100 mesh, 200 mesh, 325 mesh, etc.), the vibration frequency is controlled at 200 Hz, and the amplitude is 1 mm; during the screening process or after the screening, an antioxidant accounting for 0.1% of the total mass of the copper powder is added to the copper powder product, and the antioxidant is a combination of benzoic acid and a passivating agent CY-502 in a mass ratio of 1:3; finally, the electrolytic copper powder product for electric contacts of the present invention is packaged, and its quality grade is inspected.
[0114] The entire process adopts a closed production environment.
[0115] In this embodiment, during the screening process, a combination of benzoic acid and passivating agent CY-502 was added to improve the content of impurity elements and improve the quality of the electrolytic copper powder product of the present invention. Specific data are shown in Table 1.
[0116] After inspection, the impurity carbon, nitrogen and sulfur contents of the products of various embodiments of the present invention are shown in Table 1 below.
[0117] Table 1 Impurity carbon, nitrogen and sulfur content of electrolytic copper powder for electric contact of the present invention (unit: ppm)
[0118] plan Carbon content Nitrogen content Sulfur content Example 1 89 22 35 Example 2 164 22 21 Example 3 142 30 20 Example 4 121 23 31 Example 5 102 21 26 Example 6 168 34 24 Example 7 189 26 26
[0119] It can be seen from the data in Table 1 that the present invention, by improving the production process of electrolytic copper powder, ultimately achieves the impurity quality indicators required for electrolytic copper powder products for electrical contacts: carbon ≤ 200 ppm, nitrogen ≤ 40 ppm, sulfur ≤ 40 ppm.
[0120] The above is only an embodiment of the present invention. The commonly known technical common sense in the scheme is not described in detail here. The ordinary technicians in the relevant field are aware of all the common technical knowledge in the technical field to which the invention belongs before the application date, can obtain all the existing technologies in the field, and have the ability to apply the conventional experimental means before that date. The ordinary technicians in the relevant field can improve and implement this scheme in combination with their own abilities under the enlightenment given by this application. Some typical commonly known technologies should not become obstacles for ordinary technicians in the relevant field to implement this application. It should be pointed out that for those skilled in the art, without departing from the structure of the present invention, they can also make some adjustments and improvements, which should also be regarded as the scope of protection of the present invention, which will not affect the effect of the implementation of the present invention and the practicality of the patent. The scope of protection claimed by this application shall be based on the content of its claims, and the specific implementation methods and other records in the specification can be used to interpret the content of the claims.
Claims
1. A method for preparing electrolytic copper powder for electrical contacts, comprising the following steps: 1) Preparation of anode, cathode and electrolyte solution; 2) Electrolysis; 3) Powder dropping; 4) Powder washing; 5) Drying; 6) Screening; It is characterized in that: the anode material is high-purity cathode copper, the electrolyte is pre-purified, and the powder dropping step adopts automatic powder dropping.
2. The method according to claim 1, characterized in that The high-purity cathode copper is grade A copper or No. 1 standard copper.
3. The method according to claim 1 or 2, characterized in that: The electrolyte is pre-purified by using an integrated filter with a 160-mesh filter cloth.
4. The method according to any one of claims 1 to 3, characterized in that: The additive used in the powder washing step is selected from a combination of soap solution or a corrosion inhibitor and a polyol compound.
5. The method according to claim 4, characterized in that: The additive is a composition of soap solution and a polyol compound, the mass ratio of which is 1:5-5:1, and the composition accounts for 0.01-5% of the total mass of the copper powder.
6. The method according to claim 4 or 5, characterized in that: The powder washing step adopts an integrated washing machine.
7. The method according to any one of claims 1 to 6, characterized in that: A combined atmosphere of an inert gas and a reducing gas is used in the drying process, and the inert gas is selected from helium, neon, argon, krypton and xenon.
8. The method according to any one of claims 1 to 6, characterized in that: An antioxidant is added during the screening process, and the antioxidant is selected from a combination of benzotriazole (BTA) or benzoic acid and a passivating agent.
9. The method according to claim 8, characterized in that The additive is a composition of BTA and passivating agent CY-502, the mass ratio of which is 1:5-5:1, and the composition accounts for 0.01-5% of the total mass of the copper powder.
10. The method according to any one of claims 1 to 6, characterized in that The whole process of the method adopts a closed production environment.
Citation Information
Patent Citations
Electrolytic copper powder and manufacturing method thereof
CN102009169A
Producing method of electrolytic copper powder
CN103866352A